2009
DOI: 10.1108/03090560910976438
|View full text |Cite
|
Sign up to set email alerts
|

Buying environment characteristics in the context of e‐service

Abstract: PurposeThis study aims to examine how buying environment characteristics, which are not directly associated with price or product information, are related to overall e‐satisfaction; and how e‐satisfaction and e‐loyalty are interrelated.Design/methodology/approachA convenience sample of 366 female and male college students from three universities (East coast, Midwest and West coast) participated. Exploratory factor analysis, confirmatory factor analysis and structural equation modeling via LISREL 8.0 were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 38 publications
1
82
1
13
Order By: Relevance
“…This indicates that if people have difficulty in navigating and understanding the contents of websites, they may abandon their shopping cart or quit online shopping. The importance of site quality factors is different from results of previous studies where customer communication (Shin et al 2013), website content (Udo et al 2010), reliability (Yang et al 2004, Santos 2003, Lee and Lin 2005, assurance (Swaid and Wigand 2009), convenience (Kim et al 2009), and responsiveness (Yang et al 2004) were the important factors. The study is also different from the work of Zhou et al (2009), where only the impact of website design and service quality on trust and satisfaction were considered.…”
Section: Tandon Kiran and Sah: Customer Satisfaction As Mediatorcontrasting
confidence: 49%
“…This indicates that if people have difficulty in navigating and understanding the contents of websites, they may abandon their shopping cart or quit online shopping. The importance of site quality factors is different from results of previous studies where customer communication (Shin et al 2013), website content (Udo et al 2010), reliability (Yang et al 2004, Santos 2003, Lee and Lin 2005, assurance (Swaid and Wigand 2009), convenience (Kim et al 2009), and responsiveness (Yang et al 2004) were the important factors. The study is also different from the work of Zhou et al (2009), where only the impact of website design and service quality on trust and satisfaction were considered.…”
Section: Tandon Kiran and Sah: Customer Satisfaction As Mediatorcontrasting
confidence: 49%
“…Chutimaskul et al (2008) found that information quality refers to information on government activities, which basically should be accurate and relevant (Chutimaskul et al 2008). Many studies show that providing better information quality increases online user satisfaction (Chutimaskul et al 2008;Nusair and Kandampully 2008;Kim et al 2009;Obi 2009). In the e-commerce domain, information quality is a factor in attracting customers to access and remain on a web site (Nusair and Kandampully 2008).…”
Section: Informationmentioning
confidence: 99%
“…The concept of e-service quality is derived from that of quality of traditional services, and eservice quality can be the key important factor for online organizations with many online organizations failing due to inadequacy in that regard (Vidgen and Barnes 2002;Kim et al 2009). Collier and Bienstock (2006) conceptualized e-service quality as users' perceptions of the outcome of the service delivery and included service recovery perceptions in the event of service failure; e-service quality is recognized as a significant online factor (Santos 2003;Lee and Lin 2005;Li and Suomi 2009).…”
Section: E-service Qualitymentioning
confidence: 99%
“…Therefore, some scholars introduce customer cognition as another rese arch path. (Kim et al, 2009) [9] proved that the online servicescape positively affects customer perceived service quality and satisfaction, which leads to customer buying behavior.…”
Section: Group-buying Servicescapementioning
confidence: 99%
“…(Eroglu, Machleit, & Davis, 2003) [8] divided the online store atmospherics into high-mission-related factors and lowmission-related factors based on media richness theory. (Kim, Kim, & Kandampully, 2009) [9] divided the online store servicescape into six dimensions: convenience, customization, informality, interaction, the appearance of the site and the value of entertainment. (Lloyd C. Harris & Ezeh, 2008) [5] argued that the online servicescape should be consist of three dimensions, including aesthetic appeal, functional layout and financial security.…”
Section: Group-buying Servicescapementioning
confidence: 99%